Numerical and experimental investigations of the early injection process of Spray G in a constant volume chamber and an optically accessible DISI engine. (December 2022) - Pati, Andrea; Paredi, Davide; Welch, Cooper; Schmidt, Marius; Geschwindner, Christopher; Böhm, Benjamin; Lucchini, Tommaso; D'Errico, Gianluca; Hasse, Christian
In this work, the Engine Combustion Network Spray G injector was mounted in the Darmstadt optical-accessible engine to study phenomena typical of multi-hole, early direct-injection events in spark-ignition engines characterized by tumble flow charge motion. Dedicated experimental measurements of both in-cylinder spray morphology and flow velocities before and after the injection process were carried out to assess the adopted numerical setup under real engine conditions. A dynamic secondary breakup model from the literature was coupled with an atomization multi-motion regime model. The model was validated against state-of-the-art ECN Spray G experiments for a constant-volume chamber under low evaporating condition. Then, the simulation of the spray injection in the engine was carried out and the achieved results were compared against the experimental data. Overall, good agreement between experiments and simulations was observed for the spray morphology and velocity fields in both cases. With reference to engine calculations the intake flow was seen to induce spray asymmetry. A partial vortex generated during the intake phase on the tumble plane interacts with the spray, developing into a full vortex which induces an upward flow that stabilizes the spray. The upward flows below the intake valve increase the dilution of the plume outside the tumble plane, which therefore exhibits reduced penetration. Moreover, the intake valves protect from the energetic intake flow the recirculation vortex generated at the tip of the plumes that lie outside the tumble plane. The intake flow helps fuse the vapor fuel clouds of the individual plumes near the injector tip, obtaining a vapor fuel with a shape like that generated by a horseshoe multi-hole injector. Finally, a phenomenological model of the interaction between the multi-hole injector jets and the engine intake flow was introduced to describe the spray evolution in a typical DISI engine.